2002
DOI: 10.1093/jac/49.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of L1 and L2 beta-lactamase expression in Stenotrophomonas maltophilia

Abstract: It has been reported that Stenotrophomonas maltophilia L1 and L2 beta-lactamase expression is coordinated. We have isolated S. maltophilia mutants where (i) L1 is constitutively hyper-expressed and L2 is inducible; (ii) L2 is hyper-expressed and L1 is inducible; and (iii) L1 and L2 are constitutively hyper-expressed. The frequency of isolating type 1 and 2 mutants is c. 10(-7), indicating that promoter mutations are probably not involved and providing strong evidence that L1 and L2 expression is not, after all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 8 publications
0
35
0
3
Order By: Relevance
“…The ␤-lactamase L1 is a metallo-␤-lactamase (352), and L2 is a clavulanic acid-sensitive cephalosporinase (353). Several studies have reported differential ␤-lactamase activities among S. maltophilia isolates (16,17,56,78,147,148,153,170,227,251,374). The L1 ␤-lactamase uses a Sec export system, while the L2 ␤-lactamase uses a Tat export system for periplasmic translocation (194,271).…”
Section: Antibiotic Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The ␤-lactamase L1 is a metallo-␤-lactamase (352), and L2 is a clavulanic acid-sensitive cephalosporinase (353). Several studies have reported differential ␤-lactamase activities among S. maltophilia isolates (16,17,56,78,147,148,153,170,227,251,374). The L1 ␤-lactamase uses a Sec export system, while the L2 ␤-lactamase uses a Tat export system for periplasmic translocation (194,271).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…The isolation of S. maltophilia mutants and the generation of isogenic L1 and L2 gene knockout mutants have shown that ␤-lactamase L1 and L2 expressions are differentially regulated (16,148). The expression of the ␤-lactamases is controlled at the level of transcription by the ampR gene, positioned upstream of L2, as part of an ampR-L2 module (201,251).…”
Section: Antibiotic Resistancementioning
confidence: 99%
“…Hence, it is very likely that the L1 or L2 gene was externally acquired in either cluster A or B if the evolutionary rates are similar for the L1 and L2 genes. Avison et al presented data on the localization of the L1 and L2 genes in cells (1,2). Minkwitz and Berg have suggested that there is a reservoir of S. maltophilia strains in the natural environment (21).…”
mentioning
confidence: 99%
“…This also explains why S. maltophilia clinical isolates in our worldwide collection that are known to express ␤-lactamase constitutively at high levels (11,22) are no less susceptible to the lactivicin derivatives than are isolates with normally inducible ␤-lactamases (Table 2). Indeed, to confirm this, we tested four L1/L2-hyperproducing mutants previously derived from S. maltophilia K279a (22,27,29) and found that the MICs of both lactivicin derivatives against K279a and these mutants are the same (32 and Յ0.031 g · ml Ϫ1 , respectively, for LTV13 and LTV17). Conclusions.…”
Section: Resultsmentioning
confidence: 76%